Вай кырӟалом, эшъёс!: кырӟанъёс / люказы: Л. В. Перевозчикова, А. Г. Иванова, С. А. Ильин - Перевозчикова Л. В. (Удмуртия, 1993)
Экземпляры: ф.3 (1994) / Инвентарный номер: 37192 / Цена: / Сис.шифр: 85.313(2Рос=Удм) / Авт.знак: В 12 / ГРНТИ: 18.41.51 / ББК: 85.313(2Рос=Удм)